Effects of musical valence on the cognitive processing of lyrics - Fiveash, Anna (2014)
The effects of music on the brain have been extensively researched, and numerous connections have been found between music and language, music and emotion, and music and cognitive processing. Despite this work, these three research areas have never before been drawn together in a single research paradigm. This is significant as their combination could lead to valuable insights into the effects of musical valence on the cognitive processing of lyrics. Based on the feelings-as-information theory, which states that negative moods lead to analytic, systematic and fine-grained processing, while positive moods encourage holistic and heuristic-based processing, the current study (n = 64) used an error detection paradigm and found that significantly more error words were detected when paired with negatively valenced music compared to positively valenced music. Non-musicians were better at detecting error words than musicians, and native English speakers outperformed non-native English speakers. Such a result explains previous findings that sad and happy lyrics have differential effects on emotion induction, and suggests this is due to sad lyrics being processed at deeper semantic levels. This study provides a framework in which to understand the interaction of lyrics and music with emotion induction - a primary reason for listening to music.